The association between volition and participation in adults with acquired disabilities: A scoping review - Hagit Harel-Katz; Eli Carmeli (SAGE Publishing, 2019)
Background/objective Physical, cognitive and psychological factors such as self-efficacy and motivation affect participation in populations with acquired disabilities. Volition is defined as a person's motivation for participating in occupation. The concept of 'volition' expands similar concepts and theories, which focus mostly on cognitive processes that influence motivation. Although volition seems to affect participation, the association between these two concepts has not been examined in populations with acquired disabilities. This scoping review explored this association. Methods The literature review used a structured five-stage framework, according to predefined inclusion and exclusion criteria. Seven electronic databases (CINAHL, PsycINFO, PubMed, Web of Science, SCOPUS, The Cochrane Library-Wiley, OTseeker) and Google Scholar were searched for relevant articles, published in English from January 2001 to May 2018. Results A total of 18 articles, relating to populations with various diagnoses were included. Two directly examined volition and participation and showed a positive association between them. Other articles discussed the effect of participants' chronic condition on their volition and participation, the effect of volition on participation, or the effect on participation of an intervention addressing volition. Conclusions An acquired disability affects both volition and participation, and volition seems to affect participation among people with acquired disabilities. Few articles showed positive effects of interventions that addressed clients' volition, on participation. Further research should include additional health conditions and types of literature, to better understand the association between these concepts. This understanding will contribute to the development of occupational therapy interventions that emphasise volition, in order to improve participation outcomes.